ANALISIS KEWAJIBAN PERPAJAKAN PPH 21, PPH 23 DAN PPH 4 AYAT 2 PADA PT TAC TAHUN 2018 - Erythrina Orie Rahma, Purnawati Helen Widjaja, Nataherwin (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This research aims to determine if the company engaged in the field of real estate, PT TAC has carried out the tax obligations as stipulated in the current taxation regulations in Indonesia. Research is also conducted to test compliance in making deposits and reporting of PT TAC Tax period notification on the three aspects of the tax in fulfilling its tax obligation as taxpayer body. The results showed that PT TAC has carried out taxation obligations on these three aspects in accordance with the prevailing regulations. There is no contingent obligation for PT TAC arising in fiscal year 2018. The three aspects of taxation include PPh 21, PPh 23 and PPh 4 paragraph 2.